Impact of the quantity and quality of the skeletal muscle on survival among patients undergoing allogeneic hematopoietic stem cell transplantation. (May 2023) - Terao, Yusuke; Nakayama, Yasuhide; Abo, Masahiro; Otobe, Yuhei; Suzuki, Mizue; Koyama, Shingo; Tanaka, Shu; Kojima, Iwao; Haga, Naoto; Yamada, Minoru
Abstract: Introduction: Poor skeletal muscle function is relatively high in patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT), leading to various negative health outcomes. This study aimed to investigate the relationship between the quantity and quality of skeletal muscle before transplantation and the short-to long-term survival after transplantation in patients undergoing allo-HSCT. Methods: This retrospective cohort study included 156 patients undergoing allo-HSCT (men, 67.3 %; median age, 53 years; interquartile range, 42–61 years). The quantity and quality of the skeletal muscle were measured at the psoas major at the level of the third lumbar vertebrae using a computed tomography (CT) and were defined as psoas muscle index (PMI) and CT values (CTV), respectively. The outcome measure of this study was overall survival (OS) after allo-HSCT, and we examined the relationship between survival at three time points (6, 12, and 24 months) after transplantation, PMI, and CTV. Results: PMI was significantly associated with survival at all time points in the crude model ( P  < 0.001), and a significant association was observed in the fully adjusted model ( P  < 0.01). CTV was significantly associated with survival at all time points in the crude model ( P  < 0.05), but not in the fully adjusted model ( P  > 0.05). Conclusions: We found that the quantity and quality of the skeletal muscle before transplantation were significantly associated with OS at 6, 12, and 24 months after transplantation, showing a particularly robust association with quantity. Highlights: We found that the quantity and quality of the skeletal muscle before allo-HSCT were significantly associated with OS. These results suggest that maintaining muscle quantity and quality before transplantation is necessary to improve OS. The present findings suggest that rehabilitation interventions before transplantation may improve OS.